The Performance Analysis of OFDM-IDMA in Wireless Communication by Using an Iterative Sub-optimal Receiver Structure (International Journal of Engineering and Computer Science, 2014)
This paper provides a comprehensive study of OFDM-IDMA. Comparisons with other alternative technology such as OFDM-CDMA are provided. Cyclic Prefix reduces the ISI in the OFDM Block and MAI is reduced by IDMA in the AWGN channel. A signal-to-noise ratio (SNR) evolution technique is developed to predict the bit-error-rate (BER) performance of OFDM-IDMA by using BPSK modulation. Also, we provide simulation results in the matlab environment.